ANALISIS PENDAPATAN USAHA SUSU KAMBING ETAWA ( Capra aegagrus hircus ) CV. SERANGKAI ANUGERAH BAHTERA DI DESA MANDIANGIN BARAT KECAMATAN KARANG INTAN KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Fitriadi, Subhan; Baparki, Ahmad; Wasdiyanta (Fakultas Pertanian UVAYA Banjarmasin, 2024)
This research technically aims to determine the process of the Etawa goat milk processing business and financially to determine the amount of costs, receipts and income obtained from the Etawa goat milk processing business. The research method used is a case study on CV. A Series of Bahtera Awards in October and November 2023 with a total cost of IDR. 14,369,785,- total receipts of Rp. 24,750,000,- and total income of IDR 10,380,215